Mismanaging Knowledge and Education and their Effects on Employment in Lebanon and the Middle East - EL-Annan, Saher H. (Journal of Education and Vocational Research, 2012)
Higher education plays an integral role in preparing graduates to enter and adapt, with minimal difficulties, to the work environment. The Lebanese and the wider Middle Eastern industry players’ feedback has shed light on the increasing dissatisfaction of the employers with the quality of those who have graduated from local universities. They contend that local graduates are too steeped in theoretical knowledge, and that their technical competencies, as well as their communication and interpersonal skills are found lacking. These graduates need further extensive training before they can be ready to join the work force and adapt to the workplace environment. Hence, and due to the existing deteriorating quality of higher education in the region, there are an increasing number of unemployed graduates. This paper addresses this issue by tackling the challenges that the educational institutions face, in addition to the means that could be adopted to effectively deal with the concerns of the Arab industries.